The utilization of ELISA in early detection of cancer - Zhou , Xiaoyang (Transactions on Materials, Biotechnology and Life Sciences, 2024)
The early detection of cancer is crucial in improving treatment success rates and survival rates. The primary focus of this research is the application of enzyme-linked immunosorbent assay (ELISA) in early cancer detection, as well as the measurement methods of cancer biomarkers. It can provide an overview of the currently used cancer biomarkers and their application in ELISA. Furthermore, this research will utilize the ELISA technique to determine whether a specific substance can serve as a cancer biomarker, with a particular emphasis on its application in early cancer detection. Through a comprehensive analysis of relevant research, this research elucidates the significance of ELISA in the measurement of cancer biomarkers and its potential as a robust cancer screening tool. Finally, this research will highlight the future directions of research, focusing on the implementation of ELISA technology in detecting and identifying a wider range of cancer biomarkers for achieving more accurate early cancer diagnosis.